Breast milk polyunsaturated fatty acids: associations with adolescent allergic disease and lung function. Issue 8 (25th January 2017) - Waidyatillake, N. T.; Stoney, R.; Thien, F.; Lodge, C. J.; Simpson, J. A.; Allen, K. J.; Abramson, M. J.; Erbas, B.; Svanes, C.; Dharmage, S. C.; Lowe, A. J.
Abstract: Background: It has been hypothesized that n −3 PUFA in breast milk may assist immune and lung development. There are very limited data on possible long‐term effects on allergic disease and lung function. The aim was to investigate associations of n −3 and n −6 PUFA levels in colostrum and breast milk with allergic disease and lung function at ages 12 and 18 years. Methods: Polyunsaturated fatty acids were measured in 194 colostrum samples and in 118 three‐month expressed breast milk samples from mothers of children enrolled in the Melbourne Atopy Cohort (MACS) Study, a high‐risk birth cohort study. Associations with allergic diseases, skin prick tests and lung function assessed at 12 and 18 years were estimated using multivariable regression. Results: Higher levels of n −3 but not n −6 PUFAs in colostrum were associated with a trend towards increased odds of allergic diseases, with strong associations observed for allergic rhinitis at 12 (OR = 5.69[95% CI: 1.83, 17.60] per weight%) and 18 years (4.43[1.46, 13.39]) and eczema at 18 years (9.89[1.44, 68.49]). Higher levels of colostrum n −3 PUFAs were associated with reduced sensitization (3.37[1.18, 9.6]), mean FEV1 (−166 ml [−332, −1]) and FEV1 /FVC ratio (−4.6%, [−8.1, −1.1]) at 12 years. Conclusion: Higher levels of colostrum n −3 PUFAs were associated with increased risks of allergic rhinitis and eczema up to 18 years, and sensitization and reduced lung function at 12 years. As residual confounding may have caused these associations, they should be replicated, but these results could indicate that strategies that increase maternal n −3 PUFA intake may not aid in allergic disease prevention.